ПРИМЕРЫ АРТЕФАКТОВ В ГЕОЛОГИИ - Мизин А.И. (My University, 2003)
In the article situations at which there can be false facts are considered. The sizes of grains of the minerals, determined at the petrographic analysis, depend on orientation of a plane of a section. At data of results several scale's works there can be a seeming complexity of a structure of territory. Nonexistent structures arise at distortion of scales during construction of sections. It is necessary to take into account these situations at geological researches.
Keywords: 55:001.8